Nutritional assessments and interventions in head and neck, esophageal, rectal and lung cancers undergoing anticancer treatments: a literature review - Casalone, Valentina; Lazzari, Chiara; Fassi, Elena; Gregorc, Vanesa (Frontiers in Oncology, 2025)
In the last decades, greater toxicities deriving from anticancer treatments (especially chemo and/or radiotherapy), along with cancer sites, increase the risk of nutritional status impairment. This condition should be avoided because it could determine early therapies’ interruptions and worse clinical outcomes. In this review, we aim to provide an overview of the current evidence obtained from Pubmed and Embase databases assessing the role of nutritional assessments and interventions during anticancer treatments, with a particular focus on immunonutrition. Actual evidence suggests that nutritional practices are different worldwide, however, it is essential to define an adequate and standardized nutritional evaluation including at least food intake estimation, anthropometric measurements and body composition analysis. Nutritional interventions should always include intensive counseling and, in some cases, the prescription of specific dietary supplements. Nowadays, immunonutrition formulas represent a promising tool to improve many nutritional and treatment outcomes, but further studies are still necessary to define an evidence based clinical practice.